Social strategies used by dispersing males to integrate into a new group in Tibetan macaques (Macaca thibetana). Issue 9 (16th July 2021) - Xia, Dong‐Po; Garber, Paul A.; Sun, Lixing; Sun, Binghua; Wang, Xi; Li, Jin‐Hua
Abstract: In group‐living mammals, an individual's fitness depends, in part, on the quality of social relationships it has with others. Among species of nonhuman primates in which one sex is philopatric, individuals of that sex often develop strong social bonds and alliances with closely related kin. Less is known regarding the social processes used by dispersing adults to form stable bonds with nonkin in their new group. From May to December 2009, April to August 2010, September to December 2011, and February to May 2012, we collected data on grooming interactions in wild Tibetan macaques ( Macaca thibetana ), a female philopatric species, at Mt. Huangshan, China. Our goal was to compare social interactions and bond formation between resident males, recent immigrant males, and resident females. Our results indicate that recent immigrant males formed stable partner relationships with a small number of resident females and groomed these females more frequently or for longer than they received grooming. In contrast, resident males switched female grooming partners more frequently, received more grooming than they gave, and formed relationships with a greater number of female partners. We argue that the ability of recent immigrant male Tibetan macaques to maintain strong and persistent social bonds with a small set of resident adult females is a primary factor that enables them to establish residence in a new multimale–multifemale group. The present study provides new and important insights into the integrated social strategies used by dispersing males and resident females to maintain group stability. Abstract : Mean +/‐ SE (boxes) R indices between male‐female grooming dyads. Males were categorized as recent immigrants (white boxplot) or residents (gray boxplot). Highlights: Recent immigrant male Tibetan macaques establish strong social bonds and persistent partnerships with a small number of resident females as a social tool to integrate into their new group. In contrast, males who are long‐term residents of the group, frequently change female partners and exhibit less stable partner relationships. The study provides new and important insights into the integrated social strategies used by recent immigrant males, long‐term resident males, and resident females in maintaining group cohesion in a multimale–multifemale primate society.